2018
DOI: 10.1016/j.burns.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized burns in Finland: 36 305 cases from 1980–2010

Abstract: To analyse the epidemiology of burns in Finland, a comprehensive study was conducted among all hospitalized burn patients between 1980 and 2010. All patients with burn injury as the main diagnosis, 36305 cases in total, treated in the public and private sectors, were included. Patient data were obtained from the Finnish Hospital Discharge Register (FHDR). The incidence of hospitalized injuries declined from over 30 to 17 per 100000 persons. Men were at higher risk than women in all age groups. Children aged un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
(16 reference statements)
3
6
1
Order By: Relevance
“…This finding contrasts with most studies carried out in Western countries, in which the ratio of men to women is usually greater than 1, as in Australia (2.8) or Finland (2.3). Nevertheless, in Southern European countries, the ratio is generally found to be closer to the data found in our study, for example in Italy (1.47), Bulgaria (1.41), or Portugal (1.38) 7‐11 . This fact could be related to differences in the type of work performed by males there, predominantly risk‐related and heavy industrial jobs.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding contrasts with most studies carried out in Western countries, in which the ratio of men to women is usually greater than 1, as in Australia (2.8) or Finland (2.3). Nevertheless, in Southern European countries, the ratio is generally found to be closer to the data found in our study, for example in Italy (1.47), Bulgaria (1.41), or Portugal (1.38) 7‐11 . This fact could be related to differences in the type of work performed by males there, predominantly risk‐related and heavy industrial jobs.…”
Section: Discussionsupporting
confidence: 82%
“…The ALOS was 15.5 days, longer than that recorded in other countries such as Norway (11.3 days) 14 and Finland (12.4 days), 8 but shorter than that found in others, such as Portugal (16 days), 11 Germany (18.8 days), 15 or Italy (22 days) 9 . Age seems to have a clear influence on the characteristics, frequency, and severity of the burns.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Nordic countries, whom are similar to the Netherlands in many ways, show much higher incidence rates than those in our study. In Finland, Sweden, and Norway, incidence rates of 17.0, 15.5, and 12.4 per 100,000 inhabitants were found [ 13 15 ]. This might be explained by differences in health care system, climate, demography, and culture.…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies have shown that men are at the highest risk of both occupational accidents and burn injuries (Mian et al 2011 ; Reichard et al 2015 ; Hansen 2019 ; Hanvold et al 2019 ; Tanttula et al 2018 ). Our data showed different results: The gender distribution in the FWCC register was almost even (men 54%) but men dominated (25/26 cases) in the NBC data.…”
Section: Discussionmentioning
confidence: 99%